Self-perception of life quality and the practice of physical activity in elderly - Santos, Jorge (2019)
The aging of population is an increasingly observable fact in several developed countries. We know that this life period can mean loss of life quality due to biological losses, psychological problems and social relations. The present study intends to verify if elderly people practicing a regular program of formal physical activity have a better perception of their quality of life compared to non-practicing elderly. The number of participants consisted of 64 elderly people (n = 64), living in Proença-a-Nova, being divided into two groups of 32 elements, in which one group had formal physical activity and the one was non-practitioners. The perceived quality of life was measured using the MOS SF-36 questionnaire. The results revealed that the perception of the quality of life presents only statistically significant differences in the physical and social functions and the health change item, in which that the group of practitioners presents higher values